Toggling near-field directionality via polarization control of surface waves - Zhong, Yuhan (2022)
Directional excitation of guidance modes is central to many applications ranging from light harvesting, optical information processing to quantum optical technology. Of paramount interest, especially, the active control of near-field directionality provides a new paradigm for the real-time on-chip manipulation of light. Here, it is found that for a given dipolar source, its near-field directionality can be toggled efficiently via tailoring the polarization of surface waves that are excited, for example, via tuning the chemical potential of graphene in a graphene-metasurface waveguide. This finding enables a feasible scheme for the active near-field directionality. Counterintuitively, it is revealed that this scheme can transform a circular electric/magnetic dipole into a Huygens dipole in the near-field coupling. Moreover, for Janus dipoles, this scheme enables actively flipping their near-field coupling and non-coupling faces.